Optimized processing of Gardenia Fruits with ginger juice: Unveiling therapeutic mechanisms for cholestatic liver injury through TLR4/NF-κB, FXR/PPAR-α, and PI3K/AKT/GSK-3β - Chenzi Lyu; Xianglong Meng; Juan Wang; Haifeng Shao; Yang Wang; Yong-Ki Park; Shuosheng Zhang; Hyo Won Jung (PLoS ONE, 2025)
The study aimed to optimize the processing conditions of Gardeniae Fructus with ginger juice (GFPG) and confirm its therapeutic effects and pharmacological mechanisms on cholestatic liver injury. Processing conditions were optimized using response surface methodology (RSM) and thermal analysis, focusing on geniposide content as a key active compound. Variables included processing time, moistening time, and the solid-liquid ratio. Optimal conditions were: ginger juice to Gardeniae Fructus ratio of 8:1 (w/v), processing temperature of 208 °C, moistening time of 3 hours, and processing time of 5 minutes. Pharmacological mechanisms were analyzed through network pharmacology, molecular docking, and experimental validation using alpha-naphthyl isothiocyanate (ANIT)-induced cholestatic liver injury in mice and lipopolysaccharide (LPS)-stimulated RAW264.7 cell models. In vivo, GFPG extract alleviated ANIT-induced cholestatic liver injury by improving liver function markers (AST, ALT, TBA, TBIL, DBIL) and modulating TLR4/NF-κB, FXR/PPAR-α, and PI3K/AKT/GSK-3β pathways. In vitro, it reduced LPS-induced production of inflammatory mediators (NO, TNF-α, IL-6, IL-1β) through TLR4/NF-κB pathway inhibition. This study established optimal processing methods for GFPG using RSM and thermal analysis, providing robust quantitative parameters. GFPG demonstrated significant therapeutic effects in cholestatic liver injury models, indicating its potential as a candidate for developing treatments for cholestatic hepatitis.